Effect of soil texture and water application rate on water movement in soil profile under trickle irrigation - Ibrahim, Kaiser (University of Thi-Qar Journal of Science, 2019)
the study was conducted to know the effect of water application rate (R) and soil texture (S) on vertically and horizontally movement of water in the soil profile under triclcle irrigation two type of soil texture (S1 sandy Loam, S2 Loamy soil ) and three water application rate (R1=0.5 L/h, R2=1.0 L/h and R3= 1.5 L/h) was used.The used soil was in plastic container( 80*80)cm with plexiglass in one side of container to show the vertically movement of water clearly . The results were showed that the horizontal wet front increases with increasing the water application rate in the Loam soil as compard with sandy loam soil , but the vertically distance of wet front at the sandy loam was more than the same distance at the loam soil . The Philip (1958) one and two term equation used to fit the experimental data of wet front distance with time.Emperical equation that describe this movement were also used for the all treatment.